2000
DOI: 10.2136/sssaj2000.6462080x
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Effects on Carbon Fluxes in Continuous Wheat and Fallow–Wheat Rotations

Abstract: The traditional cropping system in semiarid regions of the Canadian prairies involves frequent summer fallowing with several tillage operations to control weeds during the fallow period. Recently, there has been a trend toward reduced tillage and more intensive cropping, but the impact of this shift in management on sequestration of atmospheric CO2 remains uncertain. In 1995 and 1996, we measured fluxes of CO2 in a tillage experiment that had been initiated in 1982 on a silt loam (Typic Haploboroll) in southwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
147
6
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(170 citation statements)
references
References 23 publications
15
147
6
2
Order By: Relevance
“…Conventional tillage has influence on soil aggregate turnover, improves soil aeration, infiltration, water holding capacity, and increases the contact between soil and crop residues, which results in increased soil CO2 emissions compared to no-tillage. Lower soil C-CO2 emissions at no-tillage compared to conventional tillage have also been determined by many other authors [15,[18][19][20][21]. Similar results were reported by Franzluebbers et al [26], who found that CO2 emissions in some years were higher in no-tillage than in conventional tillage, but in other years, the tillage effect was not observed.…”
Section: Influence Of Tillage Treatment On Soil C-co2 Emissionssupporting
confidence: 85%
See 1 more Smart Citation
“…Conventional tillage has influence on soil aggregate turnover, improves soil aeration, infiltration, water holding capacity, and increases the contact between soil and crop residues, which results in increased soil CO2 emissions compared to no-tillage. Lower soil C-CO2 emissions at no-tillage compared to conventional tillage have also been determined by many other authors [15,[18][19][20][21]. Similar results were reported by Franzluebbers et al [26], who found that CO2 emissions in some years were higher in no-tillage than in conventional tillage, but in other years, the tillage effect was not observed.…”
Section: Influence Of Tillage Treatment On Soil C-co2 Emissionssupporting
confidence: 85%
“…Conventional tillage has influence on soil aggregate turnover, improves soil aeration, infiltration, water holding capacity, and increases the contact between soil and crop residues, which results in increased soil CO 2 emissions compared to no-tillage. Lower soil C-CO 2 emissions at no-tillage compared to conventional tillage have also been determined by many other authors [15,[18][19][20][21].…”
Section: Discussionsupporting
confidence: 53%
“…9). This more pronounced aggregation increase does, however, not seem to lead to an [3,26,[30][31][32]35,38,59,65,77,79,109,111,113,114,139,164,172,173,177,194,Paustian and Elliott,unpublished,214,219,220,241] for (sub)tropical soils and from [2,11,22,42,50,[54][55][56]58,67,72,78,84,85,89,93,95,96,104,105,133,134,136,146,…”
Section: Mechanisms Of C Sequestration Under No-tillagementioning
confidence: 99%
“…As fractal coefficient h increased due to soil aggregation, more carbon could be sequestered in the soil. The effect of conservation practices [28] and crop rotation [4] [29] on carbon sequestration can thus be compared using the h parameter.…”
Section: Fractal Kineticsmentioning
confidence: 99%